Integrated Reporting: Studi Pada Perusahaan Publik di Indonesia - Febriansyah febriansyah (UNIVED Press, 2022)
The purpose of this study is to empirically test the effect stakeholder engagement which is projected with the concentration of ownership, leverage, and employee compensation as well as the independent board of commissioners and gender diversity as projections from corporate governance to the presentation of Integrated Reporting in public companies in Indonesia in the LQ 45 Group of Companies, there are 22 companies included in the research sample in accordance with the criteria of this study. The type of data used is Panel Data, data analysis uses E-Views as an analysis tool. Based on the results of analysis and testing regarding the analysis of the influence of Stakeholder Engagement and Corporate Governance mechanisms on the disclosure of the integrated report of LQ-45 companies listed on the IDX for the 2017-2019 period, empirical results are obtained in which concentration of ownership, leverage, proportion of independent board of commissioners, number of committee meetings audit and gender diversity do not have an influence on the integrated report disclosure. The positive significant relationship with the disclosure of <IR> is the employee compensation variable.